PENGARUH MANAJEMEN ASET TERHADAP OPTIMALISASI PENGELOLAAN ASET DAERAH - Bill Pangayow; Muhammad Rizky Pratama (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2016)
This study aimed to analyze the effect of an inventory of assets, legal, audit, asset valuation, as well as  the supervision and control of the asset, the asset management optimization area. Studies in Jayapura city government. This study was conducted in 29 government institutions in the city of Jayapura. Collecting data in this study is the use of questionnaires and interviews with civil servants (PNS) working in the regional work units (SKPD) Jayapura city government. The sampling technique used in this research is purposive sampling number of research samples taken as many as 66 respondents. data analysis techniques using multiple linear regression. And using SPSS 16.00. Based on the analysis using test equipment Linear Regression indicates that the asset inventory is not proven effect on the optimization of the asset management area, which means do not fit the hypothesis, individually legal audit proved positive and significant impact on the optimization of the asset management  area, individually, individually asset valuation proved no effect on the optimization of local asset management, supervision and control of assets proved to be positively and significantly to the optimization of the asset management area. While the results of the joint analysis - together / simultaneously showed that all four variables, namely an inventory of assets, legal audit, asset valuation, as well as the supervision and control of assets proved to have a significant effect / positively to optimizing the management of local assets.  Keyword: an inventory of assets, legal audit, asset valuation, monitoring and control of assets, and asset optimization